Epithelial desquamation observed in a phase I study of an oral cathepsin C inhibitor (GSK2793660). (20th September 2017) - Miller, Bruce E.; Mayer, Ruth J.; Goyal, Navin; Bal, Joanne; Dallow, Nigel; Boyce, Malcolm; Carpenter, Donald; Churchill, Alison; Heslop, Teresa; Lazaar, Aili L.
Abstract : Aims: Cathepsin C (CTSC) is necessary for the activation of several serine proteases including neutrophil elastase (NE), cathepsin G and proteinase 3. GSK2793660 is an oral, irreversible inhibitor of CTSC that is hypothesized to provide an alternative route to achieve NE inhibition and was tested in a Phase I study. Methods: Single escalating oral doses of GSK2793660 from 0.5 to 20 mg or placebo were administered in a randomized crossover design to healthy male subjects; a separate cohort received once daily doses of 12 mg or placebo for 21 days. Data were collected on safety, pharmacokinetics, CTSC enzyme inhibition and blood biomarkers. Results: Single, oral doses of GSK2793660 were able to dose‐dependently inhibit whole blood CTSC activity. Once daily dosing of 12 mg GSK2793660 for 21 days achieved ≥90% inhibition (95% CI: 56, 130) of CTSC within 3 h on day 1. Only modest reductions of whole blood enzyme activity of approximately 20% were observed for NE, cathepsin G and proteinase 3. Seven of 10 subjects receiving repeat doses of GSK2793660 manifested epidermal desquamation on palmar and plantar surfaces beginning 7–10 days after dosing commencement. There were no other clinically important safety findings. Conclusions: GSK2793660 inhibited CTSC activity but not the activity of downstream neutrophil serine proteases. The palmar–plantar epidermal desquamation suggests a previously unidentified role for CTSC or one of its target proteins in the maintenance and integrity of the epidermis at these sites, with some similarities to the phenotype of CTSC‐deficient humans.